Does structural compromise of the aorta in patients with aortic pathologies predict increased spinal and vascular complications and reoperations in patients undergoing anterior approach to the spine? - Neil V. Shah; Pelin Çeliker; Cirous Sadeghi; Rachel Baum; Juhayer S. Alam; Chibuokem Ikwuazom; Peter L. Zhou; Benjamin Krasnyanskiy; David Kim; Rohan Desai; Sandeep Bains; Jeffrey M. Schwartz; et al. (Journal of Craniovertebral Junction and Spine)
Objectives: Anterior spinal fusion (ASF) presents unique challenges, including the proximity of critical anatomic structures. Previous reports have detailed vascular injuries during exposure/approach; however, it is not well-documented whether structural aortic pathology, such as aneurysm, dissection, atherosclerosis, aortitis, or aortic tumors, impacts postoperative outcomes following anterior approach to the spine for spinal fusion. Materials and Methods: Using the New York State Statewide Planning and Research Cooperative System, thoracolumbar ASF patients with a history of aneurysm, dissection, atherosclerosis, aortitis, or aortic tumors (APath) were identified and matched to patients with no aortic pathologies (No-APath). The two cohorts were compared at 90-day and 2-year follow-up for complications, readmissions, and revisions. Multivariate binary stepwise logistic regression identified independent predictors of these outcomes. Results: Ninety-nine and 64 patients were included at 90-day and 2-year follow-ups, respectively. APath and No-APath had comparable demographics. Through 90-day follow-up, both cohorts had similar vascular complications and overall complications. No-APath patients had higher surgical complications (11.1% vs. 0%, P = 0.021). At 2-year follow-up, cohorts had comparable vascular complications, overall complications, and all other outcomes (P > 0.05). Neither group was observed to require any revisions through 2-year follow-up. The presence of a structural aortic pathology was not associated with increased odds of incurring adverse outcomes at 90-day and 2-year follow-ups. Conclusions: Structural aortic compromise in the setting of thoracolumbar ASF did not predispose patients to adverse vascular, spinal-related, or medical/surgical complications, nor to anterior spinal or vascular revision or repair through 2-year follow-up. These results highlight the need for well-powered studies to further delineate the risk of anterior spinal surgery in this cohort of patients.